Enhanced Low Voltage Ride Through Capability for Grid Connected Wind Energy Conversion System - Mohammed Alsumiri; Raed Althomali (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
It is obvious that the current era has received much attention in the fields of science and technology, besides the continuous endeavor to provide environmentally friendly and resource-saving alternatives for conventional energy conversion systems. The rapid development of Wind Energy Conversion Systems (WECS) has made Permanent Magnet Synchronous Generator (PMSG) a primer choice because of its advantages. The current trend on WECS necessitates wind turbines to maintain continuous operation during voltage drops, which is referred to as Low Voltage Ride Through (LVRT). The PMSG control technique is a widely used approach for improving conversion efficiency as well as LVRT capability. This paper provides LVRT and power enhancement for grid-connected PMSG based WECS using control techniques. The LVRT capability has been investigated by using PI and Residue controllers. The simulation results show improved active power delivery and better LVRT capability during voltage dips when the Residue controller is implemented.